Los siete años de abundancia - Keret, Etgar, 1967- (Nuevos tiempos (Madrid, Spain) ;, 2014)
The seven years between the birth of Etgar Keret's son and the death of his father were good years, though still full of reasons to worry. Lev is born in the midst of a terrorist attack. Etgar's father gets cancer. The threat of constant war looms over their home and permeates daily life.